Enhanced inhibition of murine prostatic carcinoma growth by immunization with or administration of viable human umbilical vein endothelial cells and CRM197 - Huiyong,Zhang (2011)
Vaccination with xenogeneic and syngeneic endothelial cells is effective for inhibiting tumor growth. Nontoxic diphtheria toxin (CRM197), as an immunogen or as a speciﬁc inhibitor of heparin-binding EGF-like growth factor, has shown promising antitumor activity. Therefore, immunization with or administration of viable human umbilical vein endothelial cells (HUVECs) combined with CRM197 could have an enhanced antitumor effect. Six-week-old C57BL/6J male mice were vaccinated with viable HUVECs, 1 x 10(6) viable HUVECs combined with 100 μg CRM197, or 100 μg CRM197 alone by ip injections once a week for 4 consecutive weeks. RM-1 cells (5 x 10(5)) were inoculated by sc injection as a preventive procedure. During the therapeutic procedure, 6-week-old male C57BL/6J mice were challenged with 1 x 10(5) RM-1 cells, then injected sc with 1 x 10(6) viable HUVECs, 1 x 10(6) viable HUVECs + 100 μg CRM197, and 100 μg CRM197 alone twice a week for 4 consecutive weeks. Tumor volume and life span were monitored. We also investigated the effects of immunization with HUVECs on the aortic arch wall and on wound healing. Vaccination with or administration of viable HUVECs+CRM197 enhanced the inhibition of RM-1 prostatic carcinoma by 24 and 29%, respectively, and prolonged the life span for 3 and 4 days, respectively, compared with those of only vaccination or administration with viable HUVECs of tumor-bearing C57BL/6J mice. Furthermore, HUVEC immunization caused some damage to the aortic arch wall but did not have remarkable effects on the rate of wound healing; the wounds healed in approximately 13 days. Treatment with CRM197 in combination with viable HUVECs resulted in a marked enhancement of the antitumor effect in the preventive or therapeutic treatment for prostatic carcinoma in vivo, suggesting a novel combination for anti-cancer therapy.